MY SAY: May 13 a lurking cancer cell - Abd Razak, Dzulkifli (2010)
On the 13th of this month, I was on my way to the new Bangkok airport after having participated in a UNESCO retreat in the outskirt of the city. The people who were with me had a travel advisory to go straight home after office. It did not sound like a very comfortable message but the ride to the airport was smooth and peaceful. Still, an outsider would have found such travel advisories and media coverage unsettling although the situation in the city was not what it seemed. I personally had a hard time convincing others that it was only a section of the city that was under siege. By and large, it was business as usual in Bangkok.